Features of Metaphors in Shaukat Rahman’s Poetry - Z. Sh. Ashurova (International Journal on Orange Technologies, 2023)
The article reflects on metaphor, and notes that the study of metaphor has been analyzed, in particular, by representatives of such sciences as rhetoric, psychology, philosophy, stylistics, literary criticism, translation studies and even cybernetics.